2005
DOI: 10.1002/ijc.21530
|View full text |Cite
|
Sign up to set email alerts
|

Association of a distinctive strain of Epstein‐Barr virus with gastric cancer

Abstract: Epstein-Barr virus (EBV) has been linked to gastric carcinoma (GC) with worldwide geographical variations attributable to types and variants of EBV. Here, we compare EBV strains between EBVaGC and healthy donors in Latin America, a high frequency area for EBVaGC. Tumor samples from 73 EBVaGC cases and throat washings from 329 healthy adults were examined for types 1 and 2 EBV and polymorphism at BamHI-F and BamHI-W1/I1 boundary regions and XhoI restriction site in LMP1 gene. Type 1 and prototype F of BamHI- F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 44 publications
10
66
0
1
Order By: Relevance
“…LELC constitutes only 1-4 % of all GCs [2][3][4] and has been described as having a favorable prognosis compared with that of ordinary GC, especially in LELCs with Epstein-Barr virus (EBV) infection [1,[5][6][7][8][9]. EBV infection is found in more than 80 % of LELC cases, and EBVpositive LELCs share the following features with EBVassociated GCs: male predominance, predisposition to the proximal part of the stomach, and a high proportion of diffuse-type gastric carcinomas [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…LELC constitutes only 1-4 % of all GCs [2][3][4] and has been described as having a favorable prognosis compared with that of ordinary GC, especially in LELCs with Epstein-Barr virus (EBV) infection [1,[5][6][7][8][9]. EBV infection is found in more than 80 % of LELC cases, and EBVpositive LELCs share the following features with EBVassociated GCs: male predominance, predisposition to the proximal part of the stomach, and a high proportion of diffuse-type gastric carcinomas [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is clear that these LMP1 variants are widely distributed with somewhat different frequencies in different parts of the world, but in most studies, there was no evidence for a specific association with disease (Senyuta et al 2014;Gantuz et al 2013). Other reports of LMP1 variation associated with specific populations and disease contexts, for example gastric and oral carcinoma (Chen et al 2010BenAyed-Guerfali et al 2011;Higa et al 2002), have mostly lacked sufficient numbers or control samples to interpret in the context of the relationship between variation and disease, but some studies have suggested an association with disease (Corvalan et al 2006). …”
Section: Lmp1mentioning
confidence: 96%
“…9,10 EBVaGC has been reported to be associated with rather distinct clinicopathologic features, including more predominant in men, proximal in location, diffuse subtype, and less frequent lymph node metastasis. 9,11 EBVaGC also predicts better survival of patients with GC. However, the histomorphologic features of EBVaGC are variable.…”
mentioning
confidence: 92%